Gambolling with Galatea: a Bucolic Romance - Dunham, Curtis; Herford, Oliver, 1863-1935 (Salt Lake City, UT : Project Gutenberg, 2018)
"Gambolling with Galatea: a Bucolic Romance" by Curtis Dunham is a novel written in the early 20th century. The story centers around the interactions between a group of anthropomorphized farm animals and their human counterparts, exploring themes of companionship, communication, and the humorous absurdities of life in a rural setting. The main characters include Galatea, the spirited young woman, and a variety of animals such as Clarence the colt, Reginald the pig, and Cleopatra the mare, illustrating a whimsical blend of pastoral life and comedy. The beginning of the novel introduces us to the frustrations of a young colt named Clarence, who, along with other animals, feels imprisoned while their caretaker Amanda is away. The animals band together to demand freedom, embarking on a humorous and chaotic attempt to escape. Amid their antics, we also meet the Poet and his sister Galatea, who are about to spend the summer at the farm, setting the stage for their adventures with the animated animal ensemble. This opening portion establishes a lighthearted tone and hints at the interplay between human and animal consciousness that will unfold throughout the story. (This is an automatically generated summary.)
Release date is 2018-03-28
E-text prepared by Richard Tonsing, David Edwards, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Country life -- Fiction; Human-animal relationships -- Fiction; Livestock -- Fiction